Effect of fertilization on structural and molecular characteristics of hen egg ovalbumin. (15th April 2017) - Duan, Xiang; Li, Mei; Ji, Bing; Liu, Xuebo; Xu, Xueming
Highlights: Structural change of egg ovalbumin after fertilization has been studied. New ovalbumin-related proteins X and Y emerged on day 9 of incubation. All ovalbumin spots reduced in abundance on day 15 of incubation. Abstract: Egg ovalbumin possesses high processing properties and allergenic behaviour relating to its particular molecular structure. Fertilized eggs provide a natural model for studying the structural change of ovalbumin. After fertilization, free sulfhydryl content increased from 1.03 μmol/g protein to 1.07 and 1.25 μmol/g protein on days 9 and 15 of incubation. Surface hydrophobicity of fertilized egg ovalbumin was higher than that of unfertilized egg ovalbumin (42.59), reaching 47.00 and 53.09 at 9 and 15 days. A secondary structural change occurred during this period, characterized by an increase in extended-chain segments and a decrease in intermolecular β-sheets. Hydrolysis degree of ovalbumin increased from 10.17% to 16.40% after 15 days of incubation. Furthermore, new ovalbumin-related proteins X and Y emerged on day 9, and then all ovalbumin spots reduced in abundance on day 15. These results warrant further research into the effect of fertilization on functional properties of ovalbumin.